2001
DOI: 10.1002/da.1071
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of post-traumatic stress disorder following severe injury

Abstract: The chronicity and morbidity of established post-traumatic stress disorder (PTSD) has stimulated interest in recognizing and understanding the early development of the disorder. Acute stress disorder, a new diagnosis intended to facilitate early case detection, rests on the occurrence of dissociative reactions. It remains uncertain whether dissociation is a universal or unique early predictor of subsequent PTSD. Traumatic injury is an important and relatively understudied antecedent of PTSD. The objective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 27 publications
4
52
0
1
Order By: Relevance
“…Some authors have presumed the presence of PTSD symptoms causes the use of avoidant coping (36,50). However, other authors have reported avoidant coping as a predictor of later PTSD symptoms in populations of Gulf War victims, domestic violence victims, and traumatic injury victims (51)(52)(53). A recent study measured coping strategy in 56 mothers of premature infants in the neonatal ICU (31).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have presumed the presence of PTSD symptoms causes the use of avoidant coping (36,50). However, other authors have reported avoidant coping as a predictor of later PTSD symptoms in populations of Gulf War victims, domestic violence victims, and traumatic injury victims (51)(52)(53). A recent study measured coping strategy in 56 mothers of premature infants in the neonatal ICU (31).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that nightmares may emerge after a longer interval of time where more complex emotional processing of the traumatic event has had the opportunity to occur [17], whereas insomnia may be proximally linked to, and a more immediate consequence of, acute trauma exposure [15]. However, this is not supported by other studies showing that nightmares also manifest in the immediate aftermath of trauma, and that peritraumatic nightmares often resolve [18,19].…”
Section: Insomnia and Traumatic Eventsmentioning
confidence: 91%
“…Similarly, cross-sectional studies have found avoidant coping positively associated with PTSD symptoms among war veterans (e.g., Sutker, Davis, Uddo, & Ditta, 1995), motor vehicle accident survivors (e.g., Bryant & Harvey, 1995), and victims of sexual and nonsexual assault (Dunmore, Clark, & Ehlers, 1999;Valentiner, Foa, Riggs, & Gershuny, 1996). The few longitudinal studies of the impact of coping behaviors on posttraumatic stress have also demonstrated that more avoidant coping (e.g., Benotsch et al, 2000;Mellman, David, Bustamante, Fins, & Esposito, 2001;Sharkansky et al, 2000) predicted more psychological symptoms at a later time point. However, no longitudinal study has yet included a sample of IPV survivors.…”
Section: Avoidant Coping Strategiesmentioning
confidence: 91%